The Housewife’s Resistance as Portrayed in Somerset Maugham’s Short Story Entitled `The Colonel’s Lady` - Ratna Asmarani (Universitas Muhammadiyah Semarang, 2018)
The focus of this paper is to analyze the domination and resistance in the domestic area as portrayed in Maugham‟s The Colonel’s Lady. The special aims are to analyze the factors that trigger the wife‟s resistance, the kind of resistance carried out by the wife, and the impacts of the wife‟s resistance on the husband. The analysis is supported by the concept of power by Foucault, the concepts of resistance and how to face domination by Vinthagen and Johanson, Husu, Butler et al., Cohen and Taylor, and Woolf. The qualitative method is used in the contextual analysis focusing on the character, conflict, and setting. The result shows that the wife subtly resists the constricting patriarchal atmosphere in the household by constructing a private area in which she actualizes herself in the world of poetry. Her great success enables her to enter a new and different zone where she is the star. This makes the husband feel uncomfortable and even insulted but he cannot do anything because his wife still shows her respect to him and she does nothing unlawful against him.